2018
DOI: 10.2147/cia.s157186
|View full text |Cite
|
Sign up to set email alerts
|

<em>PPARgamma-2</em> and <em>ADRB3 </em>polymorphisms in connective tissue diseases and lipid disorders

Abstract: BackgroundThe aim of the research genetic study was to investigate the association between variants (C1431T and Pro12Ala) of the peroxisome proliferator-activated receptor (PPARgamma-2) gene, Trp64Arg polymorphism of the beta-3-adrenergic receptor gene and lipid profile in Polish population including group of 103 patients with connective tissue disease (CTD) and 103 sex-and age-matched controls in context of statin use.MethodsAnthropometric and biochemical parameters were measured by routine methods, followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…A detailed description of the methodology was included in our previous studies [2,18,24]. DNA samples from patients and controls were isolated from peripheral blood lymphocytes with a Gentra Puregene Blood Kit (Qiagen, Hilden, Germany).…”
Section: Genetic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the methodology was included in our previous studies [2,18,24]. DNA samples from patients and controls were isolated from peripheral blood lymphocytes with a Gentra Puregene Blood Kit (Qiagen, Hilden, Germany).…”
Section: Genetic Evaluationmentioning
confidence: 99%
“…In this study, 111 patients were selected from patients in the Department of Rheumatology and Internal Diseases. The participants were also selected from our previous study [18]. Those patients with severe kidney and liver diseases, with infections, with untreated thyroid disorders, that are nonsmokers, with skin ulcerations during CTD, and without supplementation of minerals and vitamins were selected to the study.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the ADRB3 gene have an influence on metabolic and lipid disorders [63]. ADRB3 hypermethylation in adipose tissue of obese individuals has been linked to a greater susceptibility to visceral obesity and alteration in body fat distribution [64] and methylation in the promoter of the ADRB3 gene in visceral adipose tissue has been linked as a causal factor in the alteration waist-hip ratio, as well as the change in blood pressure in obese individuals [20].…”
Section: Discussionmentioning
confidence: 99%
“…[12] The polymorphisms of the β-3AR gene proposed in our study, have been proved to play a significant role in bodyweight elevation and dyslipidaemias. [13,14] Investigator found that, in all genetic models with random effects except HTG model, it exhibited significant associations between type 2 diabetes and rs4994 polymorphism of the β-3AR gene in Asians. [15] However, the non-Asian population demonstrated no significant association in any genetic models with random effects.…”
Section: Discussionmentioning
confidence: 99%